Clinical audit of estradiol implant therapy: Long duration of action and implications in non-hysterectomised women - Wheatley, Shaday; Bell, Robin J.; Stuckey, Bronwyn G.A.; Robinson, Penelope J.; Davis, Susan R. (Maturitas, 2016)
•Estrapel is an oestradiol implant that provides a non-oral treatment option for menopausal hormone therapy.•Its prolonged action makes patient selection important, as the implants cannot easily be removed.•In women with an intact uterus, the continuation of progestin therapy after cessation of implant therapy is imperative. We audited the files of 114 postmenopausal women who had been treated with subcutaneous Estrapel (50mg oestradiol implants). Of the 92 women who received more than one implant, the median number of days between implants was 223.5 (range 49–875), with an estimated median time to return to baseline of 311days (range 108–1228). Although oestradiol implants can provide an excellent non-oral treatment option, their prolonged action makes patient selection important, as the implants cannot easily be removed. In women with an intact uterus, the continuation of progestin therapy after cessation of implant therapy is imperative.